STUDY OF THE SEPARATION PROCESS OF INSOLUBLE RESIDUES IN THE NITRIC ACID PROCESSING OF SLUDGE WASTE FROM A SODA PLANT (E Conference Zone, 2025)
In this research work, separation of the insoluble residue, which is one of the most complicated processes during the nitric acid processing of the sludge waste of the soda enterprise, is devoted. The insoluble residue during the decomposition process consists of small crystals and has a negative effect on the filtration process. Filtering and filtering processes are not considered to be one of the technologically acceptable methods of separation of phases formed during decomposition of sludge with nitric acid in a filter press.